STRUGGLING METAL CRAFTS PRACTICE IN DARJEELING AND KALIMPONG DISTRICT OF WEST BENGAL - Mondal, Sribarna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the scenario of emerging Indian economy, Crafts-this unorganized sector become very important owing to its large number of employment generation potentiality and significant contribution towards export business. In the scenario of Darjeeling and Kalimpong district, this Sub Himalayan region is the home of many metal crafts artisans who are struggling because of gradual increasing pressure of modern machine-made products which decoy and changing metal crafts ecology are made this exquisite master pieces vulnerable. Metal crafts artisans were the main source to fulfill the demand of rural economy in these two districts but now the product is rarely present in the market. Changing consumer interest, low cost machine made and foreign products, lack of innovation towards new design trends, lack of awareness of market and support this heritage practice standing at its critical end. This study delves into metal crafts artisans called themselves Vishwakarma in Darjeeling and Kalimpong district, their present condition, crafts products, production procedure, scope of survival and farther development through the qualitative study using survey questioner and interview of artisans and other stakeholders. Findings from the data of 114 respondents from artist/producer, Retailers, Important Officials persons are exhibited, the identified issues and development areas toward future growth and survival of this crafts such as, upgradation of tools and technology, intervention initiatives and supports, welfare and marketing support, entrepreneurship and branding have been discussed. Data were collected from Darjeeling Palbazar Block, Jorbanglo Sukhia Block, Kurseong Block, Kalingpong 1.